2020
DOI: 10.1111/1346-8138.15559
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of low‐dose spironolactone and topical benzoyl peroxide in adult female acne: A randomized, double‐blind, placebo‐controlled trial

Abstract: Effective therapies for adult female acne (AFA) are limited. Oral spironolactone (SPL), 100-200 mg/day, is currently used off-label to treat AFA. However, high-dose SPL results in clinically significant side-effects which prevent widespread use in clinical practice. The efficacy of low-dose spironolactone in AFA is unknown. We examined the efficacy and tolerability of low-dose (25-50 mg/day) oral SPL in Thai women with moderate AFA. A randomized, double-blind, placebo-controlled trial was conducted for 12 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
5
0
4
Order By: Relevance
“…A randomized, double-blind, placebo-controlled trial conducted over 12 weeks, which enrolled 63 adult women aged 24-45 years, found that the combination of topical benzoyl peroxide and low-dose spironolactone (50 mg/day) was effective in improving moderate adult female acne, with an acceptable side-effect profile. Therefore, the authors proposed this regimen as an option for treating moderate adult female acne (43).…”
Section: Treatment Of Adult Female Acnementioning
confidence: 99%
“…A randomized, double-blind, placebo-controlled trial conducted over 12 weeks, which enrolled 63 adult women aged 24-45 years, found that the combination of topical benzoyl peroxide and low-dose spironolactone (50 mg/day) was effective in improving moderate adult female acne, with an acceptable side-effect profile. Therefore, the authors proposed this regimen as an option for treating moderate adult female acne (43).…”
Section: Treatment Of Adult Female Acnementioning
confidence: 99%
“…Es importante recordar que, si la paciente está embarazada o bien no lo tolera, debe de utilizar ácido azelaico (6). El peróxido de benzoilo debe estar en el tratamiento del acné de la mujer adulta ya que se ha visto una gran mejoría cuando este se combina con antiandrogénicos como la espironolactona (9). También el peróxido de benzoilo es un tratamiento muy adecuado ya que es queratolítico, tiene un efecto antibacterial y disminuye la producción de sebo.…”
Section: Diagnósticounclassified
“…Con estas dosis se logran ver mínimos o nulos efectos secundarios, los que se lograron observar fueron: Irregularidad menstrual, calambres, presiones bajas, pérdida de peso, sensibilidad mamaria, mareo (3). El monitoreo de estudios en menores de 40-45 años no es mandatorio ya que los cambios no se observan (9). Las precauciones del uso de la espironolactona son: categoría C del embarazo, la hiperpotasemia en pacientes con enfermedad renal crónica, insuficiencia cardiaca y el sangrado uterino anormal (10,15).…”
Section: Tabla 3 Escala Afast Para La Zona Mandibularunclassified
“…Todos los estudios incluidos con intervenciones basadas en espironolactona ofrecieron resultados positivos en pacientes con acné en sus diferentes grados clínicos. Aunque la efectividad por cada grupo fue variable, en los 15 manuscritos del grupo de terapia combinada y/o comparativa, solo dos (13.3%) artículos eficacia escasa 21,32 , seis estudios (40%) describieron la eficacia como moderada 20,25,26,27,30,31 mientras que siete manuscritos (46.7%) mencionaron una eficacia significativa [22][23][24]28,29,33,34 (Tabla 3). De los estudios pertenecientes al grupo de monoterapia, en un manuscrito (20%) se concluyó una eficacia moderada 39 y en cuatro (80%) artículos se encontró una eficacia significativa [35][36][37][38] (Tabla 4).…”
Section: Efectos De Las Intervencionesunclassified
“…Dieciocho de los 20 artículos que fueron incluidos en la revisión reportaron diversas reacciones adversas. Las alteraciones menstruales fueron las más comunes, 20,26,29,[30][31][32][33][35][36][37][38] seguido por la hiperkalemia, 30 pigmentación localizada en la zona en donde se utilizó la terapia tópica, 21 mareos, [24][25][26]29,33,36,37 y fatiga, 29,30,33,37 Se presentaron otras reacciones adversas con menos frecuencia (Tabla 5).…”
Section: Reacciones Adversasunclassified